CHIMERISM AFTER LIVER TRANSPLANTATION FOR TYPE IV GLYCOGEN STORAGE DISEASE AND TYPE 1 GAUCHER’S DISEASE - Starzl, Thomas E. (1993)
BACKGROUND: Liver transplantation for type IV glycogen storage disease (branching-enzyme deficiency) results in the resorption of extrahepatic deposits of amylopectin, but the mechanism of resorption is not known. METHODS: We studied two patients with type IV glycogen storage disease 37 and 91 months after liver transplantation and a third patient with lysosomal glucocerebrosidase deficiency (type 1 Gaucher’s disease), in whom tissue glucocerebroside deposition had decreased 26 months after liver replacement, to determine whether the migration of cells from the allograft (microchimerism) could explain the improved metabolism of enzyme-deficient tissues in the recipient. Samples of blood and biopsy specimens of the skin, lymph nodes, heart, bone marrow, or intestine were examined immunocytochemically with the use of donor-specific monoclonal anti-HLA antibodies and the polymerase chain reaction, with preliminary amplification specific to donor alleles of the gene for the beta chain of HLA-DR molecules, followed by hybridization with allele-specific oligonucleotide probes. RESULTS: Histopathological examination revealed that the cardiac deposits of amylopectin in the patients with glycogen storage disease and the lymph-node deposits of glucocerebroside in the patient with Gaucher’s disease were dramatically reduced after transplantation. Immunocytochemical analysis showed cells containing the HLA phenotypes of the donor in the heart and skin of the patients with glycogen storage disease and in the lymph nodes, but not the skin, of the patient with Gaucher’s disease. Polymerase-chain-reaction analysis demonstrated donor HLA-DR DNA in the heart of both patients with glycogen storage disease, in the skin of one of them, and in the skin, intestine, blood, and bone marrow of the patient with Gaucher’s disease. CONCLUSIONS: Systemic microchimerism occurs after liver allotransplantation and can ameliorate pancellular enzyme deficiencies.